2017
DOI: 10.1111/bjd.15316
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oxymatrine for treatment and relapse suppression of severe plaque psoriasis: results from a single-blinded randomized controlled clinical trial

Abstract: Treatment with oxymatrine effectively ameliorated severe plaque psoriasis, and was accompanied by only minor adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…Oxymatrine has been used to treat solid tumours, with a dose of 1000–1500 mg intravenously, once daily for 30–45 days . Moreover, our preliminary clinical findings indicated that oral 0·6 g daily oxymatrine had little effect but intravenous administration produced a significant effect . Furthermore, studies have shown that the absolute bioavailability of oxymatrine by the oral route was very low .…”
Section: Methodsmentioning
confidence: 65%
“…Oxymatrine has been used to treat solid tumours, with a dose of 1000–1500 mg intravenously, once daily for 30–45 days . Moreover, our preliminary clinical findings indicated that oral 0·6 g daily oxymatrine had little effect but intravenous administration produced a significant effect . Furthermore, studies have shown that the absolute bioavailability of oxymatrine by the oral route was very low .…”
Section: Methodsmentioning
confidence: 65%
“…Oxymatrine is a quinolizidine alkaloid isolated from the Chinese medicine Sophora flavescens and adopted to treat chronic viral hepatitis, plaque psoriasis, and arrhythmia [ 67 , 68 , 69 ]. Besides the findings of beneficial actions, it is proved to worsen liver damage.…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%
“…36 Furthermore, OMT improved lesions in patients with severe psoriasis without obvious toxicity. 37 CCK8 assays confirmed no obvious toxicity of OMT-LIP to NP cells, indicating that both OMT and OMT-LIP are safe within a reasonable concentration gradient (Figure 3A). Furthermore, OMT-LIP obviously repressed IL-1β-induced apoptosis detected by fluorescence microscope and flow cytometry, as shown in Figure 3B-D.…”
Section: Discussionmentioning
confidence: 92%